Occupational radiation exposure and cancer incidence in a cohort of diagnostic medical radiation workers in South Korea. (26th May 2021) - Lee, Won Jin; Ko, Seulki; Bang, Ye Jin; Choe, Seung-Ah; Choi, Yeongchull; Preston, Dale L
Abstract : Objectives: We investigated the association between protracted low-dose ionising radiation and the risk of cancer in medical radiation workers, the largest group of workers with occupational radiation exposures. Methods: Data of all South Korean diagnostic medical radiation workers enrolled at the National Dose Registry during 1996–2011 were merged with the death and cancer incidence data until 31 December 2017. SIRs, relative risks and excess relative risks (ERRs) for cancer were calculated to quantify the radiation dose–response relationship using Poisson regression models. Results: A total of 3392 first primary cancer cases were identified among 93 920 diagnostic medical radiation workers. The mean cumulative badge dose in the cohort was 7.20 mSv. The ERRs for solid cancer with a 5-year lag and haematopoietic cancers with a 2-year lag for all workers were 0.15 per 100 mGy (95% CI −0.20 to 0.51) and 0.09 per 100 mGy (95% CI −2.02 to 2.20), respectively. The ERRs for cancers did not significantly vary by job title, different lag years or after excluding thyroid and lung cancers. Sensitivity analyses restricted to workers employed for at least 1 year, or who were employed in or after 1996, or who had exposure to a cumulative badge dose of 1 mSv or more showed similar results. Conclusions: Occupational radiation doses were not significantly associated with cancer incidence among South Korean diagnostic medical radiation workers. However, cautious interpretation of ERRs is needed due to the limitations of short follow-up and low cumulative radiation doses.